Local hypothyroidism favors the progression of preneoplastic lesions to hepatocellular carcinoma in rats. Issue 1 (26th November 2014) - Frau, Carla; Loi, Roberto; Petrelli, Annalisa; Perra, Andrea; Menegon, Silvia; Kowalik, Marta Anna; Pinna, Silvia; Leoni, Vera Piera; Fornari, Francesca; Gramantieri, Laura; Ledda‐Columbano, Giovanna Maria; Giordano, Silvia; et al.
<x xml:space="preserve">Abstract</x> Thyroid hormone receptors (TRs) are ligand‐dependent transcription factors that mediate most of the effects elicited by the thyroid hormone, 3, 5, 3′‐L‐triiodothyronine (T3). TRs have been implicated in tumorigenesis, although it is unclear whether they act as oncogenes or tumor suppressors, and at which stage of tumorigenesis their dysregulation occurs. Using the resistant‐hepatocyte rat model (R‐H model), we found down‐regulation of TRβ1 and TRα1 and their target genes in early preneoplastic lesions and hepatocellular carcinoma (HCCs), suggesting that a hypothyroid status favors the onset and progression of preneoplastic lesions to HCC. Notably, TRβ1 and, to a lesser extent, TRα1 down‐regulation was observed only in preneoplastic lesions positive for the progenitor cell marker, cytokeratin‐19 (Krt‐19) and characterized by a higher proliferative activity, compared to the Krt‐19 negative ones. TRβ1 down‐regulation was observed also in the vast majority of the analyzed human HCCs, compared to the matched peritumorous liver or to normal liver. Hyperthyroidism induced by T3 treatment caused up‐regulation of TRβ1 and of its target genes in Krt‐19+ preneoplastic rat lesions and was associated with nodule regression. In HCC, TRβ1 down‐regulation was not the result of hypermethylation of its promoter, but was associated with an increased expression of TRβ1‐targeting microRNAs ([miR]‐27a, ‐181a, and ‐204). An inverse correlation between TRβ1 and miR‐181a was also found in human cirrhotic peritumoral tissue, compared to normal liver. Conclusion: Down‐regulation of TRs, especially TRβ1, is an early and relevant event in liver cancer development and is species and etiology independent. The results also suggest that a hypothyroid status of preneoplastic lesions may contribute to their progression to HCC and that the reversion of this condition may represent a possible therapeutic goal to interfere with the development of this tumor. (Hepatology 2015;61:249–259)